Engineering insights into heater design for oxygen reduction in CZ silicon growth - Amir Reza Ansari Dezfoli (Case Studies in Thermal Engineering)
Oxygen impurity is unavoidable during the Czochralski (CZ) growth of single silicon crystals. Currently, there are costly methods to control oxygen levels in the final silicon crystal, such as using magnets or high-quality crucibles. This paper proposes a special heater design to decrease and control oxygen concentration during the CZ process without incurring additional costs. Four distinct heater designs are analyzed for their impact on various parameters. The temperature profiles within the heaters, CZ puller, and silicon melt and crystal are studied. The research shows that heater design significantly influences temperature distributions and melt patterns, affecting oxygen distribution and its transport mechanisms. If more heat is supplied at the upper section of the crucible, oxygen solvation near the melt-free surface increases, and oxygen atoms are more likely to evaporate from the melt surface. Furthermore, shifting the high temperature to the crucible's top side wall strengthens buoyancy-thermocapillary vortices while weakening Taylor-Proudman vortices. This helps transport oxygen to the melt-free surface before it reaches the melt-crystal interface. With the optimal heater design, an oxygen reduction of 6 Ppma (parts per million atoms) was achieved by simply altering the heater design configuration.